2018
DOI: 10.1002/nur.21853
|View full text |Cite
|
Sign up to set email alerts
|

Responding to intimate partner violence: Healthcare providers' current practices and views on integrating a safety decision aid into primary care settings

Abstract: Supportive care for survivors of intimate partner violence (IPV) remains limited in primary care settings. Low-income and Spanish-speaking survivors of IPV are even more disadvantaged, given the dearth of linguistically and culturally appropriate interventions for IPV. We conducted semi-structured individual interviews with 17 healthcare workers, including physicians, nurses, and social workers, to describe how healthcare workers serving primarily low-income, Latina populations are currently screening and resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…interpersonal violence) via mobile app underscores the critical need for developers to create data protection policies and infrastructure that uphold the rigorous protection of health information. Previous research on intimate partner violence has found mobile apps designed with safety and privacy in mind to be an acceptable and feasible supplement to in-person health care visits, providing a rapid way to disclose and engage in safety planning ( Alvarez et al, 2018 ; Tarzia et al, 2017 ). Developers and researchers alike must continue to simultaneously consider how a mobile app can facilitate enhanced communication between patients and providers, while also ensuring said communication remains confidential to the appropriate security standards (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…interpersonal violence) via mobile app underscores the critical need for developers to create data protection policies and infrastructure that uphold the rigorous protection of health information. Previous research on intimate partner violence has found mobile apps designed with safety and privacy in mind to be an acceptable and feasible supplement to in-person health care visits, providing a rapid way to disclose and engage in safety planning ( Alvarez et al, 2018 ; Tarzia et al, 2017 ). Developers and researchers alike must continue to simultaneously consider how a mobile app can facilitate enhanced communication between patients and providers, while also ensuring said communication remains confidential to the appropriate security standards (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although such programs are important to primary and secondary prevention of TDV, several studies show that curriculum-based programs often do not account for variations in gender, dating history, experiences with TDV, and readiness to use skills to remain violence free or extricate themselves from present violent relationships (Fellmeth, Heffernan, Nurse, Habibula, & Sethi, 2013; Levesque, Johnson, & Prochaska, 2017). Ultimately, TDV interventions are most effective when adolescents find the interventions relevant and their implementation is sustainable (Alvarez, Debnam, Clough, Alexander, & Glass, 2018; Levesque et al, 2017).…”
mentioning
confidence: 99%
“…Another method of preventing partner violence can be found in mobile applications (apps). There are currently apps available addressing adult intimate partner violence (Alvarez et al, 2018; Glass et al, 2015; Google Play, 2018). Although numerous apps target women or health care providers seeking resources for their clients, it is not clear that the apps target teens or the unique issues this population experiences in TDV.…”
mentioning
confidence: 99%
“…Identifying IPV survivors in clinical practice may help them connect with needed support and safety services, thereby potentially reducing exposures to violence (Ali & McGarry, 2018;Anderzen-Carlsson et al, 2018;Ferranti et al, 2018). However, research has consistently demonstrated many frontline healthcare providers are uncomfortable in screening and counselling patients for IPV (Alvarez et al, 2017(Alvarez et al, , 2018Rees et al, 2014). Similarly, despite the high prevalence of IPV in Thailand and its substantial impact on health, researchers have found that Thai healthcare providers rarely ask their patients about IPV (Boonnate et al, 2015;Thananowan & Heidrich, 2008; Thananowan & Vongsirimas, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%